RESPON PUPUK PETROBIO DAN JARAK TANAM TERHADAP PRODUKTIVITAS KACANG PANJANG (VIGNA SINENSIS L.) VARIETAS KATON - Diana Indra Atmanegara; Nunuk Helilusiatiningsih; Eva Pebriana (Universitas Muhammadiyah Mataram, 2021)
Long bean is a vegetable that contains vitamins A, B, and C, fiber, minerals, and also protein. The purpose of this research was to determine the interaction between petrobio fertilizer and planting distance on long bean productivity of katon variety. The method used was a completely randomized design with 2 factors, namely petrobio fertilizer (30, 60, 90 kg/ha) and planting distance (30 x 30, 30x40, 30x50 cm). The results showed that there is interaction between petrobio fertilizer at 60 kg /ha and plant distance of 30 x 40 cm in the number of fruits at 1st, 2nd, and 4th harvests, which is as much as 5, 6, and 7 fruits.